Study into effects of a microwave field on the plant tissue - Volgusheva, Natalya; Altman, Ella; Boshkova, Irina; Titlov, Alexandr; Boshkov, Leonid (Eastern-European Journal of Enterprise Technologies, 2017)
We report results of experimental research into effects of heat treatment of different plant materials in a microwave field. The effects of seed bio-stimulation are investigated, as well as features of drying and the influence of thermal treatment on the properties of moistened straw. A procedure is proposed for calculating a threshold time of seed exposure to a microwave field, compiled on the basis of hypothesis on the emergence of a bio-stimulation effect. We identified a cascade pressure growth in a container with humid grain when the layer’s temperature exceeds 70 оС. The moisturizing effect of the lower layer of grain was established during its drying in MW field under conditions of a leakproof bottom. It is shown that at an initial moisture content in grain of 20 %, after 14 minutes of drying, the moisture content of the upper layer reached 15.5 %, of the middle layer – 14.5 %, of the lower layer – 21.6 %. It was established that performance efficiency of a microwave chamber substantially depends on the loading volume, material’s type, and moisture content. The chamber’s performance efficiency while heating water can reach 90 %, the chamber’s performance efficiency when loaded with grain does not exceed 67 %. To estimate energy effectiveness of using microwave energy, a dependence is proposed, which includes power output of the magnetron, load volume, and the value of performance efficiency. Dependences for the calculation of performance efficiency when loading a material are proposed to be established experimentally